The development of quality management system in the Scientific-medicallibrary of the Siberian State Medical University - M. V. Terekhova (Бюллетень сибирской медицины)
Issues of the development of quality management system in the scientific medical library are considered. Key idea of the quality management system is using process model of control. Essence of process approach in the library of the Siberian State Medical University is reorientation of its activity to the creation of system of the library control based upon corporative control of processes.